Prediction of BLGCC powerhouse performance accounting for off-design gas turbine operation - Manzini, Luca (My University, 2002)
Due to increasing environmental concern, it is expected that biomass usage (that causes no net emissions of CO2 to the atmosphere) will increase in the future. Biomass is however a limited resource that must be used as efficiently as possible. Conventional pulp mills currently use Tomlinson boiler powerhouse technology to raise process steam and produce electric power. Production of electric power with this technology is however not very efficient, particularly if the powerhouse includes condensing steam turbine technology. With advanced Black Liquor Gasification Combined Cycle (BLGCC) technology, an increase of plant net electric power of up to 35% could potentially be achieved. A number of former studies of pulp mills incorporating BLGCC technology assume a “simple” model for the gas turbine engine (i.e. not accounting for off-design operation of the engine when integrated in a mill powerhouse system). Such approximations can lead to significant performance estimation errors, since the gas turbine engine typically accounts for the majority of power output at a given site. In this work, more accurate modelling of the gas turbine engine is implemented, and the results (i.e. powerhouse net electric power output) are compared with those achieved on the basis of simpler gas turbine modelling procedures. The comparison is performed for two different scenarios: A scenario in which all available biofuel available at the mill-site is used in the mill powerhouse, usually leading to a situation with excess steam, which is used for on-site power generation in a condensing steam turbine unit; A fraction of the biofuel is exported, such that surplus steam generation is avoided, i.e. the BLGCC plant is configured such as to avoid low-efficiency power generation in a condensing steam turbine. The boundary conditions for the study were fixed according to available data for the KAM (“Ecocyclic Pulp Mill”) reference pulp mill. The available biofuel streams and mill process steam demands are thus set. An additional important assumption is that 30% of the ASU unit air requirements are met by bleeding air from the gas turbine compressor. The results obtained for the scenario without biomass export show that ideal, simplified performance modelling of the gas turbine unit always leads to an overestimation of the plant power output. Two main causes for this overestimation are: the effects of off-design operation of the engine; and the fact that commercially available engines are not available in sizes that exactly match the available fuel flow. Assuming the availability of an engine that is correctly sized for the available fuel flow, the performance overestimation due to neglecting off-design operation can be estimated at about 2%. Much higher inaccuracies occur when the engine is poorly matched to the available fuel flow. Furthermore, when designing such systems, it is also important to account for seasonal variations in process steam demand. This study indicates that it is important to account for such variations when selecting suitable conditions upon which to base the system design. When surplus biofuel is exported from the system, selecting an engine that is well suited to the application is even more important, given that an additional constraint is placed upon the system (i.e. avoiding surplus steam generation). In this case, a “simplified” performance estimation leads to significant differences in estimated power output and estimated potential for biofuel export. The study indicates that in this case, the system is very sensitive, and more detailed simulation tools and methods are needed to achieve accuracy for the results. Even when a well-suited engine is selected (e.g. GT10C for the case considered), large differences occur in the results generated using a simplified approach compared to using a more detailed approach. The thermodynamic potential of such a BLGCC powerhouse was also investigated. A parameter sensitivity analysis was performed to identify the best combination of gas turbine pressure ratio and firing temperature (TIT) such as to maximise plant power output. A net power output of 83.9 MW was achieved for an ideal engine operating with a pressure ratio of 25:1 and a TIT of 1673 K. This is 5.9 MW more than can be achieved by the best match available commercial engine for the same application.
Keywords: Kemiteknik; Chemical Engineering